KULIAH KERJA NYATA TEMATIK MAHASISWA FAKULTAS TEKNIK UISU DI KECAMATAN AIR PUTIH KBUPTEN BATU BARA - Luthfi Parinduri; Mhd. Zulfansyuri Siambaton; Muksin R. Harahap (Universitas Islam Sumatear Utara, 2023)
KKNT is an academic activity of higher education which is manifested through the Tri Dharma of Higher Education, namely education and teaching, research, and community service. As in the previous year, for 2023 the UISU Faculty of Engineering dispatched 159 semester VII students to carry out KKNT activities in 13 villages (out of 19 villages/wards) in Kecamatan Air Putih, Kabupaten Batu Bara. This activity lasted for 29 days from July 26 2023 to August 23 2023. The 2023 USU Faculty of Engineering KKNT carries the theme